Pola Komunikasi Interpersonal Pramuwisata di Keraton Kasepuhan Cirebon Jawa Barat - Hadi Mulyana; Zia Kemala (Tourism Scientific Journal, 2021)
This study aims to determine the effective interpersonal communication by Tour Guides at the Keraton Kasepuhan Cirebon as an educational process in conveying the historical value of the Keraton Kasepuhan Cirebon. In an effort to answer these problems, using the constructivist paradigm and qualitative descriptive methods, the researchers collected data from in-depth interviews, observations and literature studies. The analysis was carried out using an analytical model by Miles & Hubberman, namely through the process of data reduction, data presentation and conclusion drawing/verification. Effective interpersonal communication namely openness, empathy, supportive attitude, positive attitude, and equality. it well. all qualities have been executed optimally.